Risk Factors For Hypertension On Productive Age Group In Alak Health Center, Kupang City - Nalu, Asmarita Hona; Sir, Amelya Betsalonia; Ndoen, Honey Ivon (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2024)
Introduction: Hypertension is a non-communicable disease that is one of the leading causes of premature death in the world. Hypertension mostly occurs in the elderly group, but recently it is found in the productive age group, especially at the age of 20-44 years. The purpose of the study was to determine the risk factors for hypertension in productive age group in the working area of Alak Health Center, Kupang City in 2023.Methods: The analytical observational research with a case control design was used. The study was conducted in the working area of the Alak Health Centre in Kupang City in November-December 2023. The population in the study was divided into the case (productive age 20-44 years who had hypertension) and the control (productive age 20-44 years who did not suffer from hypertension). The risk factors studied were risky diet (high fat, salt and sugar), obesity and light physical activities. Data were collected through interviews using structured questionnaires. Data analysis was conducted in chi square tests.Results: The results showed that 3 risk factors of hypertension incidence in the productive age group were risky diet (OR = 4.448, 95% CI = 1.675-11.811, p = 0.003,), obesity (OR = 5.073, 95% CI = 1.994-12.903, p=0.0001), and light physical activity (OR = 6.250, 95% CI = 2.425-16.108; p = 0.002).Conclusion: The risk factors for hypertension among the productive age group in Alak Health Center working area, Kupang, were diet high in fat, salt and sugar, obesity and light physical activity.